Effect of palm oil carotene on breast cancer tumorigenicity in nude mice - Nesaretnam, Kalanithi; Radhakrishnan, Ammu; Selvaduray, Kanga Rani; Reimann, Karin; Pailoor, Jayalakshmi; Razak, Ghazali; Mustafa Mahmood, Mina; Dahliwal, Jasbir Singh (AOCS Press, 2002)
Biological therapies are new additions to breast cancer treatment. Among biological compounds, β-carotene has been reported to have immune modulatory effects, in particular, enhancement of natural killer cell activity and tumor necrosis factor-alpha production by macrophages. The objective of this study was to investigate the effect of palm carotene supplementation on the tumorigenicity of MCF-7 human breast cancer cells injected into athymic nude mice and to explore the mechanism by which palm carotenes suppress tumorigenesis. Forty-eight 4-wk-old mice were injected with 1 ×106 MCF-7 cells into their mammary fat pad. The experimental group was supplemented with palm carotene whereas the control group was not. Significant differences were observed in tumor incidence (P < 0.001) and tumor surface area and metastasis to lung (P < 0.005) between the two groups. Natural killer (NK) cells and B-lymphocytes in the peripheral blood of carotene-supplemented mice were significantly increased (P < 0.05 and P < 0.001, respectively) compared with controls. These results suggest that palm oil carotene is able to modulate the immune system by increasing peripheral blood NK cells and B-lymphocytes and suppress the growth of MCF-7 human breast cancer cells.